Giant Pleural Hydatid Cyst: A Case Report - Sudarto, Sudarto; Belinda, Selli; Fathurrachman, Alif; Andriani, Linda; Pasaribu, Rouly; Rasyid, Ahmad; Ahmad, Zen; Setiawan, Tommy (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: Echinococcosis is a zoonotic disease caused by the larva stage of a Taeniidae parasite of Echinococcus. Echinococcus granulosus (E. granulosus) causes cystic echinococcus (CE) and is the most common species causing disease in humans. A pleural hydatid cyst should be considered initially with a corresponding chest radiograph. It can develop into fatal complications, including secondary infection, severe bleeding, bronchial rupture and pleural or pericardial cavities. This case report shows a rare case of a pleural hydatid cyst. Case: We reported a 59-year-old woman with shortness of breath and a productive cough for three months. The chest radiography and computed tomography (CT) scan revealed a cystic lesion measuring 14.2 x 18.5 cm with edge calcification thick around 3 mm. The pleural histopathology revealed that the cyst wall was made of fibrocollagen with a red oval echinococcus. The patient received oral albendazole/ABZ (400mg BID) for three months, paracetamol (500mg TID), and n-acetylcysteine (200mg TID). After three months, the patient had no complaints, only shortness of breath with heavy activity. Conclusion: It is important to be aware of this condition to avoid inappropriate and potentially dangerous underdiagnoses and treatment, which could endanger the patient.